2023
DOI: 10.1093/jscr/rjad109
|View full text |Cite
|
Sign up to set email alerts
|

Migratory biliary stent resulting in colonic perforation: a rare complication and review of literature

Abstract: Biliary stent insertion during endoscopic retrograde cholangiopancreatography is used as a therapeutic intervention allowing flow of bile into the duodenum. In rare circumstances, distal gastrointestinal perforation can be attributed to a migrated biliary stent, with the most common site being the sigmoid colon. In these cases, surgical and/or endoscopic intervention may be required. We report a case of a 98-year-old male presenting with small bowel obstruction secondary to migrated plastic and metal biliary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“… 9 The most reported risk factor for stent-migration–associated colonic perforation is diverticulosis, followed by adhesions, hernias, and strictures. 1 In one study that identified 37 cases of colonic perforations secondary to migrated stents, they found that 62% of the cases had diverticular disease, as in our case. 1 Moreover, plastic biliary stent type may affect the risk of bowel perforation.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“… 9 The most reported risk factor for stent-migration–associated colonic perforation is diverticulosis, followed by adhesions, hernias, and strictures. 1 In one study that identified 37 cases of colonic perforations secondary to migrated stents, they found that 62% of the cases had diverticular disease, as in our case. 1 Moreover, plastic biliary stent type may affect the risk of bowel perforation.…”
Section: Discussionsupporting
confidence: 57%
“… 1 In one study that identified 37 cases of colonic perforations secondary to migrated stents, they found that 62% of the cases had diverticular disease, as in our case. 1 Moreover, plastic biliary stent type may affect the risk of bowel perforation. Double-pigtail biliary stents may prevent bowel perforation because of their pliable and soft plastic compared with the straight tip of straight biliary stents.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations